EFEKTIFITAS AIR REBUSAN DAUN SIRIH DALAM MEMPERCEPAT PENYEMBUHAN LUKA PERINEUM DI BPM WILAYAH KERJA PUSKESMAS KESAMBEN, KABUPATEN JOMBANG - Nur Farida, Siti; Dian Anggraini, Rista; Fatmawati, Istiadah (LPPM STIKES HUSADA JOMBANG, 2023)
Piper betle contains kavikol which can be used to traditional treatments, such as for deadly germs, antioksidasi, fungicidal and anti fungal. In this research want to known function kavikol who have an antiseptic in expedite the healing of injured perineum on the postpartum which is used at the vulva hygiene. The research method consists of three stages, the first stage is to do the extraction of Piper betle to get kavikol with the technique of boiling it for 10, 15 and 20 min with a temperature of 100 C and perform chemical tests and characteristics. The second stage is the implementation of utilization of kavikol extract for vulvar hygiene on the postpartum against the perineum healing wounds speed. Conclusion the results of the research are the highest levels of kavikol found on the boiling of water decoction of Piper betle with a time of 20 minutes and of the results of the data retrieval as well as observation of the 19 respondents who obtained up to date 9 November obtained data that wound stitches perineum at postpartum mother cured and dry up on day 3-4 post!, as well as no signs of infection, whereas results from interviews with respondents obtained information that respondents said pain in the perineum wound stitches also quickly reduced and feels more kesat. The results obtained from test results T from this research is the significance level of 0.000 so can be drawn the conclusion that the water decoction of leaves of the betel (Piper betle) is effective against speed healing of wounds mother postpartum on perineum